2006
DOI: 10.1518/001872006779166370
|View full text |Cite
|
Sign up to set email alerts
|

An Accurate Method for Determining the Conspicuity Area Associated With Visual Targets

Abstract: The findings are applicable to industries in which target detectability needs to be assessed in order to either reduce (e.g., for camouflage) or enhance detectability (e.g., road safety).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
7
1
Order By: Relevance
“…Our finding that both the HVA and VMA emerge gradually as we move from the HM to the VM further challenges the idea that there is a constant upper versus lower visual field asymmetry. For instance, changes in performance across isoeccentric locations have been described simply as an ellipse (e.g., Anderson, Cameron & Levine, 2014;Engel, 1971;Pretorius & Hanekom, 2006). Although the horizontal elongation of the elliptical performance field can capture the strong HVA we found in SF sensitivity, an elliptical model cannot capture the robust VMA between upper and lower visual fields observed in the present study, as well as in other studies (e.g., Abrams et al, 2012;Cameron et al, 2002;Corbett & Carrasco, 2011;Fuller et al, 2008;Montaser-Kouhsari & Carrasco, 2009).…”
Section: Discussioncontrasting
confidence: 60%
“…Our finding that both the HVA and VMA emerge gradually as we move from the HM to the VM further challenges the idea that there is a constant upper versus lower visual field asymmetry. For instance, changes in performance across isoeccentric locations have been described simply as an ellipse (e.g., Anderson, Cameron & Levine, 2014;Engel, 1971;Pretorius & Hanekom, 2006). Although the horizontal elongation of the elliptical performance field can capture the strong HVA we found in SF sensitivity, an elliptical model cannot capture the robust VMA between upper and lower visual fields observed in the present study, as well as in other studies (e.g., Abrams et al, 2012;Cameron et al, 2002;Corbett & Carrasco, 2011;Fuller et al, 2008;Montaser-Kouhsari & Carrasco, 2009).…”
Section: Discussioncontrasting
confidence: 60%
“…Previous measurements of the conspicuity area (e.g., Engel, 1971; Pretorius & Hanekom, 2007) have suggested that the visual performance field is simply an ellipse. The HVA derived from the present data illustrates the horizontal elongation of the elliptical performance field; however, an elliptical model cannot capture the robust VMA.…”
Section: Discussionmentioning
confidence: 95%
“…The shape of the visual performance field, with eccentricity held constant, is characterized by a Horizontal–Vertical Anisotropy (HVA), in which performance is better in the East 1 and West relative to the North and South, and a vertical meridian asymmetry (VMA), in which performance is better in the South than in the North. These performance fields emerge in contrast sensitivity and spatial resolution tasks (Altpeter, Mackeben, & Trauzettel-Klosinski, 2000; Anderson, Wilkinson, & Thibos, 1992; Cameron, Tai, & Carrasco, 2002; Carrasco, Talgar, & Cameron, 2001; Carrasco, Williams, & Yeshurun, 2002; Low, 1943a, 1943b; Lundh, Lennerstrand, & Derefeldt, 1983; Mackeben, 1999; Millodot & Lamont, 1974; Montaser-Kouhsari & Carrasco, 2009; Pointer & Hess, 1989; Pointer & Hess, 1990; Regan & Beverley, 1983; Rijsdijk, Kroon, & van der Wildt, 1980; Robson & Graham, 1981; Rovamo et al, 1982; Seiple et al, 2004; Silva et al, 2008; Silva et al, 2010; Skrandies, 1985; Talgar & Carrasco, 2002), as well as in visual search tasks (Carrasco, Giordano, & McElree, 2004; Chaikin, Corbin, & Volkmann, 1962; Kristjánsson & Sigurdardottir, 2008; Kröse & Julesz, 1989; Najemnik & Geisler, 2008, 2009; Pretorius & Hanekom, 2007; Rezec & Dobkins, 2004). Both the HVA and the VMA also exist in the rate of information accrual at isoeccentric locations: information accrual is faster along the horizontal than the vertical meridian, and it is faster along the lower than the upper vertical meridian (Carrasco, Giordano, & McElree, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The two effects have been described by Carrasco and colleagues and called the "horizontal-vertical anisotropy" and the "vertical meridian asymmetry" [2,[4][5][6][7][8]. Such effects, often called performance fields, are found in numerous tasks, including contrast sensitivity and spatial resolution [5,6,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] (Fig 1), visual search [24][25][26][27][28][29][30][31], crowding [32][33][34], motion perception [35], visual short-term memory [36], contrast appearance [7] and spatial frequency appearance [37]. These effects can be large.…”
Section: Psychophysical Performance Differs With Visual Field Positionmentioning
confidence: 99%